Complement factor B/C2 in molluscs regulates agglutination and illuminates evolution of the Bf/C2 family. Issue 12 (24th September 2019) - Peng, Maoxiao; Li, Zhi; Niu, Donghong; Liu, Xiaojun; Dong, Zhiguo; Li, Jiale
Abstract : Complement factor B/C2 family (Bf/C2F) proteins are core complement system components in vertebrates that are absent in invertebrates and have been lost by numerous species, raising evolutionary questions. At least 3 duplication events have occurred from Cnidaria (ancestor) to mammals. Type II Bf/C2 genes appeared during separation of Proterostomia and Deuterostomes. The second event occurred during separation of vertebrates and invertebrates, yielding type II‐2 Bf/C2. The third event occurred when jawed and jawless fish were separated, eventually producing Bf and C2 genes. Herein, we report the second mollusc Sinonovacula constricta Bf/C2‐type gene ( ScBf ). ScBf is similar to Ruditapes decussatus Bf‐like because both lack the first complement control protein module at the N terminus present in mammalian Bf/C2 proteins. Uniquely, the Ser protease (SP) module at the C terminus of ScBf is ~50 aa longer than in other complement factor B/C2‐type (Bf/C2T) proteins, and is Glu‐rich. Bf/C2T proteins in molluscs lack the catalytic Ser in the SP module. Surprisingly, ScBf regulates rabbit erythrocyte agglutination, during which it is localized on the erythrocyte surface. Thus, ScBf may mediate the agglutination cascade and may be an upstream regulator of this process. Our findings provide new insight into the origin of the Bf/C2F.—Peng, M., Li, Z., Niu, D., Liu, X., Dong, Z., Li, J. Complement factor B/C2 in molluscs regulates agglutination and illuminates evolution of the Bf/C2 family. FASEB J. 33, 13323–13333 (2019). www.fasebj.org